Tai Chi Chuan and Baduanjin Mind-Body Training Changes Resting-State Low-Frequency Fluctuations in the Frontal Lobe of Older Adults: A Resting-State fMRI Study - Tao, Jing; Chen, Xiangli; Liu, Jiao; Egorova, Natalia; Xue, Xiehua; Liu, Weilin; Zheng, Guohua; Li, Ming; Wu, Jinsong; Hu, Kun; Wang, Zengjian; Chen, Lidian; et al. (Frontiers in Human Neuroscience, 2017)
Age-related cognitive decline is a significant public health concern. Recently, non-pharmacological methods such as physical activity and mental training practices have emerged as promising low-cost methods to slow the progression of age-related memory decline. In this study, we investigated if Tai Chi Chuan (TCC)and Baduanjin can modulate the fractional amplitude of low-frequency fluctuations (fALFF) in different frequency bands (low-frequency: 0.01-0.08 Hz; slow-5: 0.01–0.027 Hz; slow-4: 0.027–0.073 Hz) and improve memory function. Older adults were recruited for the randomized study. Participants in the TCC and Baduanjin groups received 12weeks of training (1 hour / day and 5 days / week). Participants in the control group received basic health education. Each subject participated in memory tests and fMRI scans at the beginning and end of the experiment. We found that compared to the control group, 1) TCC and Baduanjin groups demonstrated significant improvements in memory function;2) TCC increased fALFF in the dorsolateral prefrontal cortex in the slow-5 and low-frequency bands; and 3) Baduanjin increased fALFF in the medial prefrontal cortex in the slow-5 and low-frequency bands. This increase was positively associated with memory function improvement in the slow-5 and low-frequency bands across the TCC and Baduanjin groups. Our results suggest that TCC and Baduanjin may work through different brain mechanisms to prevent memory decline due to aging.